Development of UPLC-MS/MS method for quantification of cefazolin and flucloxacillin for quality analysis of OPAT elastomeric pumps - Snæfríður Dröfn Pétursdóttir 1992- (2019)
Background: Outpatient antimicrobial parenteral therapy (OPAT) is an effective and a widely accepted treatment method which allows patients, who otherwise had to be hospitalized for weeks, to be discharged earlier and complete their antibiotic treatment safely outside the hospital. OPAT was implemented in The National University Hospital of Iceland in 2017 where cefazolin and flucloxacillin are amongst the most common antibiotics given with OPAT. The antibiotics are given through continuous infusion using elastomeric infusion pumps. No quality assessment has been carried out for this kind of treatment in Iceland and therefore it is important to evaluate the effectiveness of OPAT in order to ensure the safety and quality of this treatment option. Objective: To optimize an UPLC-MS/MS method for simultaneous quantification of cefazolin and flucloxacillin in OPAT pumps utilizing design of experiments. Method: Design of experiment (DoE) was used in the development of UPLC-MS/MS quantification method where screening and optimization of the process parameters was applied. In addition, method validation was performed for cefazolin in support of the analytical method. Results: UPLC-MS/MS method was developed and optimized with experimental design. The method was used to measure a sample of cefazolin solution from an elastomeric pump and its concentration was determined. Pre-validation was performed for cefazolin where results were within acceptance criteria. Flucloxacillin did not show acceptable results and was therefore not validated. Conclusion: An analytical method was successfully developed for cefazolin and a pre-validation performed. Full validation should be performed in order to confirm the quality of the method. Further development is needed for flucloxacillin and the method should be revised before performing a validation. No significant results were acquired for quality analysis of OPAT pumps due to a limited time. Further evaluation is needed in order to ensure safety and effectiveness of OPAT therapy. ...